Economics and Mathematical Relationship: A Case Study in University Economics Course of Nepal - Upadhyaya, Yadav Mani (Interdisciplinary Journal of Management and Social Sciences, 2021)
In our teaching program and methods, the mathematical approach has a major influence on economics. In this paper, I examined the aforementioned economics and mathematical relationships, taking into account their historical development as well as the experience gained over several years in the Masters in Economics Sciences’ economics course. Changes in the initial practices in the classroom entering university have prompted a rethinking of a number of fundamental questions, including: What parameters should be used to determine the most suitable curriculum and teaching approach in a changing environment? What mathematical singularities does economics teaching present? This last question introduces us to the topic we’ll be discussing. How much math should be taught in economics classes? Is it important for students to have a strong mathematical foundation before they study economics? For some teachers, economic issues are merely an addendum to the practical portion of the topic, while for others; economic models are the subject’s main focus. As a consequence, mathematics in general is now assisting in the analysis of economics. In conclusion, as students study economics, it becomes more difficult for them to study other mathematics topics. Since not all students excel at math, economics is a more difficult subject to study. However, studying algebra, calculus, and logarithms, among other subjects, makes economics more important.